HASIL BELAJAR SISWA SMA PADA PEMBELAJARAN FISIKA MENGGUNAKAN MODEL PROBLEM BASED LEARNING (PBL) DENGAN PENDEKATAN STEM (SCIENCE, TECHNOLOGY, MATHEMATICS AND ENGINEERING) - Yullya Erlina Eka Putri; Albertus Djoko Lesmono; Ismanto Ismanto (Universitas Jember, 2020)
Abstract: This article discusses the learning outcomes of high school students using the Problem Based Learning (PBL) model with the STEM (Science, Technology, Engineering and Mathematics) approach. The purpose of this article is to describe how student learning outcomes in the cognitive domain in learning physics at SMA Negeri 2 Jember using the PBL model with the STEM approach. This type of research uses true experiment research and the sample of this study is students of class X MIPA 6 in SMA Negeri 2 Jember. Data collected through the method of Student Worksheets (LKS) and tests. The instrument used in this study was a student learning achievement test in the form of a posttest. The data obtained were analyzed using the N-gain test in order to know the increase in student learning outcomes before and after using the PBL model with the STEM approach. The results of this study is the use of the PBL model with the STEM approach can improve student learning outcomes X MIPA 6 in SMA Negeri 2 Jember.